Impact of Geriatric Assessment and Management on Quality of Life, Unplanned Hospitalizations, Toxicity, and Survival for Older Adults With Cancer: The Randomized 5C Trial. Issue 4 (1st February 2023) - Puts, Martine; Alqurini, Naser; Strohschein, Fay; Koneru, Rama; Szumacher, Ewa; Mariano, Caroline; Monette, Johanne; Hsu, Tina; Brennenstuhl, Sarah; McLean, Bianca; Wills, Aria; Berger, Arielle; et al.
Abstract : PURPOSE: American Society of Clinical Oncology recommends that older adults with cancer being considered for chemotherapy receive geriatric assessment (GA) and management (GAM), but few randomized controlled trials have examined its impact on quality of life (QOL). PATIENTS AND METHODS: The 5C study was a two-group parallel 1:1 single-blind multicenter randomized controlled trial of GAM for 6 months versus usual oncologic care. Eligible patients were age 70+ years, diagnosed with a solid tumor, lymphoma, or myeloma, referred for first-/second-line chemotherapy or immunotherapy or targeted therapy, and had an Eastern Cooperative Oncology Group performance status of 0-2. The primary outcome QOL was measured with the global health scale of the European Organisation for the Research and Treatment of Cancer QOL questionnaire and analyzed with a pattern mixture model using an intent-to-treat approach (at 6 and 12 months). Secondary outcomes included functional status, grade 3-5 treatment toxicity; health care use; satisfaction; cancer treatment plan modification; and overall survival. RESULTS: From March 2018 to March 2020, 350 participants were enrolled. Mean age was 76 years and 40.3% were female. Fifty-four percent started treatment with palliative intent. Eighty-one (23.1%) patients died. GAM did not improve QOL (global QOL of 4.4 points [95% CI, 0.9 to 8.0] favoring the control arm). There was also no difference in survival, change in treatment plan, unplanned hospitalization/emergency department visits, and treatment toxicity between groups. CONCLUSION: GAM did not improve QOL. Most intervention group participants received GA on or after treatment initiation per patient request. Considering recent completed trials, GA may have benefit if completed before treatment selection. The COVID-19 pandemic may have affected our QOL outcome and intervention delivery for some participants.